(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
With the rapid development of short video technologies and the intelligent evolution of tourism e-commerce platforms, promotional videos have become a critical medium for attracting customers and driving conversion. However, due to the experiential and emotional nature of tourism products, consumers are highly sensitive to the embedded cues of “e-commerce politeness” in video content. Missteps in tone, cultural representation, or perceived authenticity can trigger trust deficits and adversely affect purchase decisions. This study investigates the impact of e-commerce politeness in tourism promotional videos on customer conversion behavior. To achieve this goal, we adopted the Critical Incident Technique, a qualitative method well-suited for capturing specific and influential user experiences. Through an online survey, we collected 263 valid incidents, including 126 positive and 137 negative cases. These incidents were systematically categorized into five positive dimensions—emotional engagement, formal innovation, audiovisual expression, cultural core, and technology-driven design—and six negative dimensions—content authenticity, perceived experience, scene rationality, cultural representation, stylistic rendering, and production quality. Data analysis revealed that audiovisual expression was the most influential positive factor (23.81%), effectively stimulating travel intention. Conversely, content authenticity emerged as the most prominent negative factor (27.94%), underscoring the risk of expectation gaps. Inter-coder reliability scores (R = 0.923 for positive incidents; R = 0.874 for negative incidents) validated the robustness of the classification framework. This study contributes to the theoretical understanding of e-commerce politeness in digital tourism marketing and offers actionable insights for video content creators, destination marketers, and platform operators. By aligning video content with customer expectations and cultural sensitivities, tourism e-commerce stakeholders can enhance trust, improve conversion rates, and foster more meaningful customer engagement.